Bone marrow involvement in sarcoidosis: an elusive extrapulmonary manifestation. Issue 2 (4th March 2019) - Peña-Garcia, J. Isaac; Shaikh, Sana; Barakoti, Bhishma; Papageorgiou, Christos; Lacasse, Alexandre
ABSTRACT: Sarcoidosis is a granulomatous disease with various extrapulmonary manifestations. We describe a 51-year-old African American woman with a history of cutaneous sarcoidosis admitted with bicytopenia. Suspicion for systemic sarcoidosis was established after contrast-enhanced computerized tomography of the chest, abdomen and pelvis showed a pulmonary nodule, diffuse lymphadenopathy and hepatosplenomegaly. Cytopenias in sarcoidosis, when present, may reflect bone marrow infiltration. Hence, biopsy was obtained and bone marrow sarcoidosis was diagnosed. This manifestation, in spite of ethnic and gender predilection, is rarely seen. As with other forms of sarcoidosis, treatment comprises of corticosteroids. Abbreviations: ANCA: Antineutrophil cytoplasmic antibody; BM: Bone marrow; BMS: Bone marrow sarcoidosis; CT: Computerized tomography; HIV: Human immunodeficiency virus; HLA: Human leukocyte antigen; MRI: Magnetic resonance imaging